Perencanaan Set-Up Proses Pemesinan Rahang Tetap dan Gerak Ragum-125 Politeknik Manufaktur Bandung: Indonesia - Diratama, M Yazid; Prakosa, Tri; Ananto, Gamawan; Riadi, Agus (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2024)
Ragum-125 Polman, is one among other different products produced by Polman Bandung which functions as a clamping device. The Ragum-125 Polman is assembled from several components where the fixed jaw and moving jaw are its main components. For the time being, the production process of the Ragum-125 Polman, especially the fixed and moving jaws, still uses many conventional machines tools and requires many jigs (locating devices) and fixtures (fixing devices). Consequently, the processing time is long. The production process requires fourteen (14) set-ups and many stages of the process from one machine to other machines, which is prone to process errors. CNC machine tools can do many machining operations in a single set-up and can minimize process errors because their movements are numerically controlled. However, to take advantage of CNC machine tools, good set-up planning is needed so that the process can be conducted according to the specifications. This research discusses the planning set-up and choosing the machine tools for machining the fixed and moving jaw of Ragum-125 Polman. It consists of four stages they are, grouping the feature according to the tool approach direction (TAD), selection the set-up datum, set-up formation, and determination the machine tools and sorting the machining operation in every set-up. The result from this research produced 19 rules for guidance the set-up planning processes and yield 2 set-ups for fix jaw and 1 set-up for moving jaw with Mitsubishi CNC Horizontal Milling Machine H4Bn and the drilling machine lodiflex Caser F40 C5 as the machine tools which reduce the number of set-ups from 14 set-up to 3 set-up in machining processes of fix jaws and moving jaws of Ragum-125 Polman.